Motivations and Challenges in Choosing Ophthalmology: A Systematic Review of Global Evidence - Yadav, Niraj Kumar; Abbasi, Sadaf; Priya, Priyanshi; Arya, Ajay Kumar; Singh, Swati; Ragunath, Reshma (Futurity Medicine, 2026)
Aims: To systematically synthesize global evidence on the motivational drivers, perceived advantages, challenges, and systemic factors influencing the choice of ophthalmology as a postgraduate medical specialty. Study Design: Systematic review conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Place and Duration of Study: This review represents a synthesis of global literature rather than a geographically bounded investigation. Studies published between January 2000 and December 2025 was included to capture evolving trends in postgraduate ophthalmology training and workforce development. Methodology: A comprehensive literature search was performed across PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar. Quantitative, qualitative, and mixed-method studies examining career motivation, mentorship, gender equity, educational exposure, and professional satisfaction in ophthalmology were included. Two independent reviewers conducted screening, data extraction, and quality appraisal using validated tools (Newcastle–Ottawa Scale, CASP, and AMSTAR-2). Narrative synthesis was undertaken due to heterogeneity in study designs and outcome measures. Results: Sixty studies met inclusion criteria for qualitative synthesis, with twenty-five contributing quantitative data. Ophthalmology was consistently associated with high intrinsic motivation, intellectual stimulation, surgical precision, and patient-centered outcomes. Key facilitators included early educational exposure, structured mentorship, and research engagement, while barriers comprised limited curricular representation, gender inequities, and inconsistent institutional support. Studies emphasizing mentorship and equity-oriented policies demonstrated improved recruitment and retention across diverse settings. Conclusion: The choice of ophthalmology as a postgraduate specialty is shaped by an interplay of intrinsic motivation, mentorship, educational exposure, and systemic support. Targeted educational reforms, mentorship frameworks, and equity-driven policies are essential to sustain a diverse and motivated ophthalmology workforce globally.